Changing women's lives and livelihoods: motorcycle taxis in rural Liberia and Sierra Leone. Issue 3 (27th June 2019) - Jenkins, Jack; Mokuwa, Esther Yei; Peters, Krijn; Richards, Paul
Abstract : In rural Liberia and Sierra Leone about half of the motorcycle taxi passengers are female, with this number rising further during market days. But all motorcycle taxi operators in rural areas are men. This study assesses if and how motorcycle taxis have contributed to the livelihoods of rural women and whether there is an appetite among them to become operators themselves. Data was gathered through male and female focus group discussions, road-side traffic counts and operator and passenger surveys. The study was conducted in three districts in rural Sierra Leone and in one rural county in Liberia. The Liberia field-site was the location of a pioneering 'upgrading footpaths to motorcycle accessible tracks' GIZ funded pilot project, connecting remote villages to the feeder road network. Both men and women were involved in track construction, and we assessed whether women's involvement made them more likely to take up commercial motorcycle riding. Women nearly universally praise the rural motorcycle taxi, indicating that it has made access to markets and (maternal) health much easier. But while many wanted to become operators themselves, they identified a number of barriers, with the lack of friends or business persons willing to rent out motorcycles to female operators the most significant one.